Economic growth dynamics of the East African region - P. Kamara (Вестник университета)
The article is devoted to the description of the dynamics of the economic development of the East African states. The paper gives a description of the current economic situation of the East African countries, lists the states included in the East African region, gives the economic and geographical characteristics of the studied region. The author also analyses the evolution of the sectoral composition of gross domestic product (GDP) of the East African countries, considers the economic factors that influence the economic growth of the states of the region. The study analyses the problem of employment and unemployment in the East African countries. The paper considers the ways of improving the economic development of the region, in particular, economic diversification, inclusive growth and structural transformation, as well as structural and institutional measures that would encourage productive investment in the economy.